1986
DOI: 10.1128/aem.52.6.1273-1279.1986
|View full text |Cite
|
Sign up to set email alerts
|

Action of citrinin on bacterial chromosomal and plasmid DNA in vivo and in vitro

Abstract: Citrinin, a mycotoxin of Penicillium citrinum and other species of the genera Penicillium and Aspergillus, caused the following effects at different concentrations in Escherichia coli. In vivo at 100 ,ug/mI single-strand breaks were caused in the chromosomal DNA. In the presence of 100 ,ug/ml, UV (254 nm)-induced DNA damage was repaired in the bacterial cells without need for a complete growth medium. At 300 ,ug/ml lambda ts prophage was induced in a lysogenic E. coli strain. In an E. coli strain carrying a F'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, the earlier reports regarding the role of oxidative stress in CIT toxicity were inconsistent. Martin et al (1986) reported that oxidative stress played a great role in causing CIT toxicity as CIT induced single- and double-strand breaks in the DNA of intact Escherichia coli and this activity was prevented by catalase and SOD, suggesting the involvement of free radicals in the mechanism of CIT-induced damage. Ribeiro et al (1997), however, did not observe any significant role of oxidative stress in CIT toxicity on rat liver cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the earlier reports regarding the role of oxidative stress in CIT toxicity were inconsistent. Martin et al (1986) reported that oxidative stress played a great role in causing CIT toxicity as CIT induced single- and double-strand breaks in the DNA of intact Escherichia coli and this activity was prevented by catalase and SOD, suggesting the involvement of free radicals in the mechanism of CIT-induced damage. Ribeiro et al (1997), however, did not observe any significant role of oxidative stress in CIT toxicity on rat liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…Natural occurrence of CIT was reported from various parts of India in various agricultural products like coconut (1.04% samples) (Kumari and Nusrath, 1987), rice (Chary and Reddy, 1987), cereals (Bilgrami et al, 1984; Pande et al, 1990), certain herbal medicinal plants (0.01–0.76 mg/g) (Chourasia, 1995), groundnut (0.65–0.90 µg/g) (Mehan and McDonald, 1984). Although involvement of specific enzymes is yet to be ascertained, oxidative stress has been found to play an important role in CIT toxicity (Martin et al, 1986; Ribeiro et al, 1997). Apoptosis, an important process in a wide variety of different biological systems, is also associated with chemical-induced cell death (Cohen, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Citrinin did not induce SOS responses in Escherichia coli PQ37 with or without S9 mediated metabolic activation (Malaveille et al, 1991;Sakai et al, 1992), and was negative in Bacillus subtilis rec assay (Ueno and Kubota, 1976). However, citrinin caused single-strand breaks in the chromosomal DNA of Escherichia coli and induced DNA repair synthesis in permeabilized E.coli cells (Martin et al, 1986).…”
Section: Genotoxicitymentioning
confidence: 99%
“…Citrinin was known more widely as a nephrotoxin in animals and, during the past two or more decades, many functional studies have been performed to elucidate its cytotoxic mechanisms resulting from interference with energy generation causing a decreased cellular ATP level, facilitation of superoxide anion production in the respiratory chain, and perturbation of the iron redox cycle (Chagas et al, 1992;Hoehler et al, 1996;Stormer & Hoiby, 1996;Ribeiro et al, 1997Ribeiro et al, , 1998Da Lozzo et al, 1998, 2002. Ueno & Kubota (1976) and Martin et al (1986) reported that citrinin has a DNA-attacking ability in vitro or in vivo. Initially, we suspected increased swarm motility of strain 681 by citrinin to be a mutational event.…”
Section: Discussionmentioning
confidence: 99%